Social Status of Tribal Women in West Bengal - Das, Prof. (Dr.) Soma; Chakraborty, Bipul (Journal of Innovation in Education and Social Research, 2024)
In the multidimensional social set up of India, empowerment of women more specifically of the tribal women need to be addressed to conceptualise the growth of the Indian societies. Empowerment includes various parameters including Education. In this review work, the educational status, Gross Enrolment Ratio (GER), Gender Parity Index, Educational age and Literacy levels of tribal women have been compared with their male counterpart as well as with the non-tribal women community. The relevant literatures from three districts of West Bengal have been reviewed in this study. The review report indicates huge inequality in educational status of the tribal women which in turn reflected in their low standard of living, poor health condition, low socio-economic status and marked discrimination in the ownership of productive resources. In the end some empowerment approaches for the tribal women have been recommended which could be implemented by the policy makers, local self-government as well as the tribal families at the individual level to promote tangible growth in the empowerment and rights of tribal women